Perolehan Flesch Reading Ease dari Cerpen Bahasa Inggris Menggunakan N-Gram - Paramtapa, Anak Agung Advaita; Husada, Milda Gustiana; Pardede, Jasman (e-Proceeding FTI, 2022)
ABSTRAK Penelitian ini menjelaskan bagaimana menerapkan metode N-Gram dalam meninjau perolehan nilai Flesch Reading Ease pada cerpen berbahasa Inggris. Nilai FRE diperoleh berdasarkan data uji berupa cerpen berbahasa Inggris serta dukungan berupa kamus kata-kata bersuku yang digunakan dalam N-Gram. Formula Flesch Reading Ease digunakan untuk memperoleh nilai keterbacaan. Hasil penelitian menunjukkan bahwa, dari 40 cerpen yang diuji, 39 cerpen memiliki nilai Flesch Reading Ease di atas 100. Selain itu, waktu pemrosesan dipengaruhi oleh banyaknya kata dalam satu cerpen. ABSTRACT This study explains how to apply the N-Gram method in reviewing the acquisition of Flesch Reading Ease scores in English short stories. This study utilizes test data in the form of short stories in English and supporting data in the form of a dictionary of syllable words to crossexamine the results of cutting data using N- Gram. In reviewing readability, one formula is used in the Flesch-Kincaid Readability Level method which is still used in research involving documents. This formula, known as the Flesch Reading Ease, is used to find the readability value of a short story by utilizing a computer system using the N-Gram method. The results showed that, of the 40 short stories tested, 39 out of 40 short stories had a Flesch Reading Ease score above 100, while the recount results showed that there was one short story with a value above 100. In addition, processing time was influenced by the number of words in one short story.